POSTOPERATIVE INTENSIVE THERAPY FOR ESOPHAGEAL ATRESIA AND ITS TRACHEOESOPHAGEAL FORMS IN NEONATES (Modern education and development, 2025)
Esophageal atresia and its tracheoesophageal forms in newborns require complex intensive therapy after surgical intervention. This article discusses post-operative resuscitation measures, airway management, artificial ventilation methods, and strategies for preventing infectious complications. Based on international research and advanced clinical experience, optimal care principles for newborns are analyzed. Modern approaches to intensive therapy contribute to improving patients' quality of life and accelerating the recovery process.